Noi contro tutti: la solidarietà aggressiva nella web communitas No Lombroso - Maria Teresa Milicia (EtnoAntropologia)
In November 2009 the renewed  display of the Museum  “Cesare Lombroso” opened to visitors in Turin. A “No Lombroso” cartel of Neo-bourbon and other Southern political associations moved to protest against the Museum. They went to  demand the repatriation of the brigand’s Villella skull for burial in his birthplace Motta Santa Lucia (CZ). In September 2012, I entered the No Lombroso Facebook group to conduct my online participant observation. The involvement in the day-to-day Facebook interactions highlights the performative construction of the aggressive solidarity into the web communitas.